Equine papillomavirus detection in aural plaques by qPCR - Zakia, Luiza S; Herman, Mariana; Hernadez, Juliana M.; Araujo Jr., Joao P.; Borges, Alexandre S.; Oliveira-Filho, Jose P. (Brazilian Journal of Veterinary Pathology, 2019)
Papillomatosis occupy a prominent position both in human and veterinary medicine, since it is a viral skin disease with potential to develop malignancy. Equus caballus papillomavirus (EcPV) are associated with several diseases in horses, i.e. classical papillomatosis associated with EcPV 1; squamous cell carcinoma associated with EcPV 2; tumors in mucous membranes on the genital area (EcPV 2 and EcPV 7); aural plaque associated with EcPV 1, 3, 4, 5 and 6; and equine sarcoid, associated with bovine papillomavirus (BPV 1 and 2). The aural plaque is characterized by small papules (1-2 cm), hypochromic and keratinized on the internal surface of the pinnae and can evolve and coalesce into larger lesions. To obtain a specific diagnostic test, both sensitive and fast to identify these viruses, a quantitative real time PCR (qPCR) was standardized for EcPV 3, 4, 5 and 6. Applying the qPCR technique in the 103 equine aural plaque samples resulted in 90.29% of at least one viral type prevalence, which was distributed as following: EcPV3, 36.89%; EcPV4, 82.52%; EcPV5, 0.97%; and EcPV6, 10.68%. This study represents an evolution in the area related to aural plaque and equine papillomatosis and raises new questions for future research.